Study on the effects of exogenous hormone and hairy roots induction in Boesenbergia rotunda for compounds production / Suzilawati Abdullah Sani - Suzilawati, Abdullah Sani (2012)
Boesenbergia rotunda is a medicinal plant belongs to the family of Zingiberaceae which contains major compounds that exhibits pharmaceutical activities. In this study, the methods of plant growth regulators and hairy roots transformation for in-vitro root culture induction in B. rotunda were established. Regenerated roots morphology and compounds accumulation in in-vitro roots and hairy roots induced were also analyzed. Media containing either NAA alone or in combinations with BAP at different concentrations (0, 0.5, 1.0, 2.0 mg/ mL and 0, 0.5, 1.0, 1.5, 2.0 mg/ mL of NAA and BAP, respectively) were used to initiate in-vitro roots. The highest number of roots was 16.5 ± 3.4 per explant, when 0.5 mg/ mL NAA was used. For hairy roots transformation, B. rotunda apical meristem was infected using A. rhizogenes strain A4. The effects of infection times (20 mins and 1 hr), co-cultivation periods (1, 2, 3 days) and acetosyringone (AS) on the transformation were investigated. Based on PCR, amplification of rolC gene analysis, infection times of 20 mins to 1 hr followed by 2 days of co-cultivation period in the presence of 10 5M AS in the cultivation media resulted in 33.3% of transformation efficiency. The profile and content of compounds in in-vitro and hairy roots were evaluated using HPLC analysis. HPLC peaks of alpinetin, pinocembrin, cardamonin, pinostrobin and panduratin A were identified and quantified. In-vitro roots induced from plant growth regulators exhibited higher bioactive compounds content as compared to controls and hairy roots induced via transformation. Supplementation of 0.5 mg/ mL NAA in MS media showed higher accumulation of alpinetin, pinocembrin, cardamonin and panduratin A, while combination of BAP and NAA with similar concentration (0.5 mg/ mL) showed higher pinostrobin content as compared to control. It is also found that exogenous PGR, enhanced the production of cardamonin contents as compared to natural rhizome.